IFN‐γ promotes τ phosphorylation without affecting mature tangles. Issue 10 (8th July 2015) - Li, Andrew; Ceballos‐Diaz, Carolina; DiNunno, Nadia; Levites, Yona; Cruz, Pedro E.; Lewis, Jada; Golde, Todd E.; Chakrabarty, Paramita
ABSTRACT: Inflammatory activation precedes and correlates with accumulating τ lesions in Alzheimer's disease and tauopathies. However, the relationship between neuroinflammation and etiology of pathologic τ remains elusive. To evaluate whether inflammatory signaling may promote or accelerate neurofibrillary tangle pathology, we explored the effect of recombinant adeno‐associated virus (rAAV)‐mediated overexpression of a master inflammatory cytokine, IFN‐γ, on τ phosphorylation. In initial studies in primary neuroglial cultures, rAAV‐mediated expression of IFN‐γ did not alter endogenous τ production or paired helical filament τ phosphorylation. Next, we tested the effect of rAAV‐mediated expression of IFN‐γ in the brains of 2 mouse models of tauopathy: JNPL3 and rTg4510. In both models, IFN‐γ increased 1) signal transducer and activator of transcription 1 levels and gliosis, and 2) hyperphosphorylation and conformational alterations of soluble τ compared with control cohorts. However, sarkosyl‐insoluble phosphorylated τ levels and ubiquitin staining were unaltered in the IFN‐γ cohorts. Notably, IFN‐γ‐induced τ hyperphosphorylation was associated with release of the inhibitory effect of glycogen synthase kinase 3β function by decreasing Ser9 phosphorylation. Our data suggest that type II IFN signaling can promote τ phosphorylation by modulating cellular kinase activity, though this is insufficient in accelerating neuritic tangle pathology.—Li, A., Ceballos‐Diaz, C., DiNunno, N., Levites, Y., Cruz, P. E., Lewis, J., Golde, T. E., Chakrabarty, P. IFN‐γ promotes τ phosphorylation without affecting mature tangles. FASEB J. 29, 4384‐4398 (2015). www.fasebj.org